2006
DOI: 10.1007/s10071-006-0017-8
|View full text |Cite
|
Sign up to set email alerts
|

Weber's Law influences numerical representations in rhesus macaques (Macaca mulatta)

Abstract: We present the results of two experiments that probe the ability of rhesus macaques to match visual arrays based on number. Three monkeys were first trained on a delayed match-to-sample paradigm (DMTS) to match stimuli on the basis of number and ignore continuous dimensions such as element size, cumulative surface area, and density. Monkeys were then tested in a numerical bisection experiment that required them to indicate whether a sample numerosity was closer to a small or large anchor value. Results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
82
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 56 publications
9
82
1
1
Order By: Relevance
“…This finding contrasts with previous research on numerical bisection with nonhumans, which typically has obtained BPs at the geometric mean (e.g., Fetterman, 1993;Jordan & Brannon, 2006b;Meck & Church, 1983;Roberts, 2005).…”
Section: Representation and Response Rulescontrasting
confidence: 99%
“…This finding contrasts with previous research on numerical bisection with nonhumans, which typically has obtained BPs at the geometric mean (e.g., Fetterman, 1993;Jordan & Brannon, 2006b;Meck & Church, 1983;Roberts, 2005).…”
Section: Representation and Response Rulescontrasting
confidence: 99%
“…For instance, values of 0.51 and 0.60 were obtained for rhesus monkeys using a similar delayed match-to-numerosity task [46]. In a forced-choice delayed match-to-sample protocol, Jordan & Brannon [68] reported Weber fractions of 0.47 and 0.48 for rhesus monkeys. In this study, it was also shown that monkeys improved their precision due to training with decreasing Weber fractions from 0.58 to 0.32.…”
Section: (B) Precision and Speed Of Numerosity Discriminationsmentioning
confidence: 99%
“…Importantly, Weber's law applies only to the perception of properties that can be described as having a magnitude [40]. Weber's law is a particularly robust psychophysical phenomenon-having been shown to hold in tasks ranging from sensorimotor judgements of weight [39,41] to cognitive tasks involving estimates of the number of objects in a sample [42].…”
Section: A Role For Weber's Law In Vibrissal Sensingmentioning
confidence: 99%